Survey of mobility prediction in wireless network - Ying WANG; Zhuang SU (Tongxin xuebao)
Smart cities based on cloud computing,big data and artificial intelligence have become important development trends.Mobile prediction is the key technology of smart city.Firstly,in order to summarize the mobile prediction methods and its applications in wireless network,the importance and feasibility of mobile prediction were stated.And the datasets of mobile prediction were introduced.Secondly,the users’ trajectory characteristics and the method of mobile prediction were summarized and compared.Finally,the problems and challenges for mobility prediction were pointed out.